Mapping of Tsunami Vulnerability Levels and Planning of Shelter Points and Evacuation Routes along the Palabuhanratu Coastline - Zafira, Aura Putri; Sutoyo; Putra, Heriansyah; Erizal; Ramadhanis, Zainab (UIR PRESS, 2025)
The Palabuhanratu Subdistrict, located in the Sukabumi Regency, is a high-risk area for tsunami disasters owing to tectonic activity along the Indo-Australian and Eurasian Plate subduction zones. The tsunami vulnerability level in this subdistrict is further heightened by the relatively dense population in its coastal areas, which increases the potential for loss of life and material losses. Therefore, an analysis of tsunami vulnerability levels and the planning of structural mitigation measures—such as shelters and evacuation routes—are crucial to protect communities from tsunami threats. This study aims to analyse the inundation area and affected population under tsunami scenarios with wave heights of 10, 15, and 20 m; identify the coverage of the proposed tsunami shelters; and evaluate the effectiveness of evacuation routes leading to the shelters in the Palabuhanratu Subdistrict. The methods employed include scoring and weighting techniques, Model Builder tools, and Network Analyst. The results indicate that coastal villages, such as Citepus, Jayanti, and Palabuhanratu, are highly vulnerable to tsunamis. Based on inundation modelling, Palabuhanratu Village had the largest inundated area and the highest number of affected residents. Most residents of Citepus and Jayanti Villages are located more than 1,350 m from the nearest shelter, with travel times exceeding 30 min. In contrast, the majority of residents in Palabuhanratu Village can reach shelters within 20 min, although some are still categorised as being in distant and very distant zones. A total of 11 evacuation routes were designed to connect the initial evacuation points to the shelters. However, 2 of the 11 routes, from Point 5 and 6, still exceed 1.000 m in distance and require more than 20 min of travel time.